The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.24036/jelt.v9i1.107932
|View full text |Cite
|
Sign up to set email alerts
|

Task Types Found in the Textbooks“bahasa Inggris: When English Rings a Bell”and Bright an English Course for Junior High School

Abstract: This research is a descriptive research that is aimed to describe the task types and to see the frequent task types that appeared in the textbooks entitled “Bahasa  Inggris: When English Rings a Bell” and Bright an English Course for junior high school.  The data was gained by using a data format. The data format is a table to classify the types the task types found in the textbooks. The data format is adapted from Nunan’s typology of task (1999). The result of this research revealed that most of the task type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Brainstorming activity such an excellent strategy to involve learners in generating their own ideas through accessing the prior knowledge. Besides brainstroming is an ideal activity done in simple way because it takes little time and can be used with any choosen topic (Ghabanchi & Behrooznia, 2014;Huda et al, 2021). Next, finding Inferrence activity is another reading-related activity that discovered in the textbook.…”
Section: Reading-related Activities In the English Textbookmentioning
confidence: 99%
See 1 more Smart Citation
“…Brainstorming activity such an excellent strategy to involve learners in generating their own ideas through accessing the prior knowledge. Besides brainstroming is an ideal activity done in simple way because it takes little time and can be used with any choosen topic (Ghabanchi & Behrooznia, 2014;Huda et al, 2021). Next, finding Inferrence activity is another reading-related activity that discovered in the textbook.…”
Section: Reading-related Activities In the English Textbookmentioning
confidence: 99%
“…Based on the explanantion above, it can be councluded that reading-related activities that discovered in the textbook are expected to students' reading comprehension. The quality of textbooks can be measured from the tasks provided in the textbook (Dewantara et al, 2022;Huda et al, 2021). In the first dimension which about language and grammar, the most frequent readin-related activities that included in the textbook are skimming/scanning, reference, and lexical item.…”
Section: Reading-related Activities In the English Textbookmentioning
confidence: 99%
“…The Indonesian Ministry of Education has arranged for English materials/textbooks from elementary school to all levels of education High school can be used directly in the teaching process. Bahasa Inggris textbook for the Eleventh Grade of Senior High School is one of the examples of The Indonesian Ministry of Education's published book (Huda et al, 2021;Liansari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was found that each textbook emphasizes one or two tasks that the writers believe are crucial for language learning. Huda and Syafei (2020) also discovered the tasks in the When English Rings A Bell and Bright textbook using Nunan's typology. The result showed that When English Rings A Bell, the frequent tasks that appear are interpersonal, linguistic, affective, creative, and cognitive.…”
Section: Introductionmentioning
confidence: 99%